The return to spendor in the world the Christian doctrine of sin and forgiveness - Gestrich, Christof; Bloesch, Daniel W. (Grand Rapids, MI Eerdmans, 1997)
Includes bibliographical references and indexes.
Translation of Die Wiederkehr des Glanzes in der Welt, Tubingen, Germany : J.C.B. Mohn (Paul Siebeck), 1989
Keywords: Sin; Good and evil; Forgiveness of sin